2020
DOI: 10.22363/2313-1683-2020-17-3-491-503
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Social Maturity Criteria, Self-perception and Value Orientations among Russian Millennials

Abstract: The difference between generations is becoming increasingly apparent in the modern world. These days, one can observe over and over again how the intergenerational transmission of values is violated, and the differences between generations are becoming more and more noticeable. A number of studies are focused on the features that distinguish modern generations from each other, the values of generations as well as the perception of these values both by a particular generation and members of cohorts interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
4
0
6
Order By: Relevance
“…In particular, the research of V.P. Pryadein showed that in the period of early adolescence and maturity, the predominance of such qualities as sociocentrism, awareness, results-oriented, internality, satanism, egotism in the structure of responsibility was noted [1,2]. Each of these qualities, which were noted to be related to the quality of responsibility, will be of great importance in the formation of maturity.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In particular, the research of V.P. Pryadein showed that in the period of early adolescence and maturity, the predominance of such qualities as sociocentrism, awareness, results-oriented, internality, satanism, egotism in the structure of responsibility was noted [1,2]. Each of these qualities, which were noted to be related to the quality of responsibility, will be of great importance in the formation of maturity.…”
Section: Introductionmentioning
confidence: 98%
“…Each of these qualities, which were noted to be related to the quality of responsibility, will be of great importance in the formation of maturity. In particular, a person's tendency to evaluate his behavior from a social point of view (sociocentrism), to have a clear idea of the outcome based on conscious motives in each case (awareness, result-oriented), the tendency to search for the causes of events in his life (internality), the predominance of activity-stimulating emotions (satanism) is undoubtedly embodied as important signs of psychological maturity [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, modern scientific and technological progress is characterized by continuous innovations and reaches such a level that requires a specialist to pursue continuous development, and, accordingly, continuous professional and personal growth. In turn, pedagogy currently provides opportunities for young people, using which they will be able to meet the requirements of modern society completely, although it is worth noting the diminishing humanitarian component of higher education, which can have a negative effect on the innovative component of the educational process (REZNICHENKO MERZLYAKOVA, GOLUBEVA & BIBARSOVA, 2020;RIKEL, 2020). Indeed, as noted by a group of scientists from High Point University (USA), choosing the right pedagogy is the first step towards the correct mastery of knowledge by a student (SAHAGUN ET AL., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Представления о взрослении стабильно остаются камнем преткновения в вопросе конфликта поколений в силу очевидной значимости этой темы в русле взаимодействия между «отцами» и «детьми». Здесь играет роль не только фактор психологической сложности перехода во взрослое состояние у подростка и отображение этой сложности в семейных отношениях: масло в огонь «подливает» социальный контекст, формирующий различное представление о взрослости у разных поколений (Рикель, 2019;Rikel, 2020).…”
unclassified